Semi-Regular Group Divisible Designs For Smaller Block Size (International Journal of Innovative Research in Computer Science & Technology, 2024)
A group divisible (GD) design is said to be  Singular (S) if ; Semi regular (SR) if  and rk – v = 0; Regular (R) if  and . In the paper, a new procedure of  constructing SRGD design with and , is  proposed from a parent SRGD after reducing number  of treatment and same number of blocks without  disturbing its Semi-Regularity property. It privileges  the experimenters to decrease the number of treatment  without affecting the number of blocks. Such designs  are useful in civil engineers, Agricultural experiments  and others. AMS Subject Classification: 05 B05
Keywords: Semi-Regular Group Divisible design; Balanced Incomplete Block design; orthogonal array